Partial study of the neuraminidase enzyme in bacteria Bacteroides fragilis isolated from patients with chronic tonsillitis in the city of Al-Diwaniyah - Abdullah Wawi Al-Shabbani, Hiyam; Ghaly Yousif, Maitham (Al-Qadisiyah Journal of Pure Science, 2018)
112 patients underwent a tonsillitis and 224 tonsil submitted during the period from October 2014 to May 2015. The patients’ ages ranged from (3-40) years, 63 (56.25%) case were males and 49 (43.75%) were females. Tonsils were divided into two groups first (112) tonsil, and it was obtained 30 isolates of Bacteroides fragilis percentage 26.78% of the total 112 tonsil,diagnosed by bacteriological standard and technical roads polymerase chain reaction (PCR) The other group (112) has been getting it on (57) isolation of B.fragilis diagnosed by direct polymerase chain reaction technique (Direct PCR) and both molecular methods were using gene diagnostic (nanH). The use of quality Primers in the PCR and Direct PCR techniques to investigate gene nanH responsible for coding for the enzyme neuraminidase, The results showed that the possession of all isolates (30) isolation of the gene nanH in the PCR technique, the technique of the Direct PCR showed 57 isolates which from (112) tonsil nanH possess the gene and thus the Direct PCR technique gave a higher proportion of roads bacteriological standard to isolate B.fragilis.